The Factors Related to the Incident of Diarrhea in Elementary School Children in Muara Burnai Village II - Ditha Effriyanda; Dini Arista Putri; Imelda Gernauli Purba; Rahmatillah Razak; Amrina Rosyada (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Poor snack food habits with a diversity of snacks encourages children's snack habits at school, because they can spend a third of their time at school. However, there are still many children who have the habit of consuming snacks and poor hand and nail hygiene habits The purpose of this study was to determine the factors associated with the incidence of diarrhea in elementary school. This research was quantitative with the Cross Sectional method. The sample in this study amounted to 118 respondents, which were determined by simple random sampling technique. Respondents were dominated by women as many as 77 respondents (65.3%), and the age of the respondents was dominated by the age category 11-12 years as many as 60 respondents (50.8%). Bivariate analysis resulted that there was a significant relationship between the frequency of snack food consumption, the choice of snack foods, the habit of washing hands, and cleanliness of nails with the incidence of diarrhea, while the habit of carrying lunch had no significant relationship with the incidence of diarrhea in elementary school in Muara Burnai Village II. The results of the multivariate analysis showed that the selection of snack foods was the most dominant variable influencing the incidence of diarrhea in elementary school children with (p-value=0.030; PR=29.291; CI 95%)=1.393-615.854) after controlling for the variable frequency of snack food consumption, washing habits hand and nail hygiene. The schools should make regulations related to standards for traders so that they become healthy canteens in school.